2004
DOI: 10.1021/jp049240h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stacking on Hydrogen Bonding:  Quantum Chemical Study on Pyridine−Benzene Model Complexes

Abstract: The present work focuses on the influence of aromatic stacking on the ability of an aromatic nitrogen base to accept a hydrogen bond. Substituent effects were studied at the MP2 level for 10 complexes of a substituted benzene stacked with pyridine in a parallel offset conformation. The interaction energies between each substituted benzene and pyridine were analyzed in terms of Hartree-Fock, correlation, and electrostatic contributions. It appears that the basicity of pyridine is directly related to the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
109
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 115 publications
8
109
2
Order By: Relevance
“…Although TvNH lacks a general acid, it is equally catalytically proficient to nucleoside hydrolases from other sources (17). We have previously shown that, instead of employing general acid catalysis, TvNH activates the leaving purine base by increasing the N7 basicity (hence favoring its protonation) via a parallel aromatic stacking interaction with the indole side chain of Trp-260 (8,24). The high level ab initio calculations presented here rule out a previously presumed stabilizing catalytic interaction between 5ЈO and 4ЈO.…”
Section: Discussionmentioning
confidence: 63%
“…Although TvNH lacks a general acid, it is equally catalytically proficient to nucleoside hydrolases from other sources (17). We have previously shown that, instead of employing general acid catalysis, TvNH activates the leaving purine base by increasing the N7 basicity (hence favoring its protonation) via a parallel aromatic stacking interaction with the indole side chain of Trp-260 (8,24). The high level ab initio calculations presented here rule out a previously presumed stabilizing catalytic interaction between 5ЈO and 4ЈO.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, both BH&H and MP2/6-31G(0.25)* perform much better than the MP2/ aug-cc-pVDZ calculations reported in ref. 24, where binding energy is overestimated on average by of 5.27 kJ mol Ϫ1 . Sinnokrot and Sherrill ascribed the trends in binding energy along this series to the subtle interplay of electrostatic, dispersion, and exchange forces.…”
Section: Resultsmentioning
confidence: 96%
“…Geerlings and coworkers 24 have achieved similar results, analysing the stacking of substituted benzene-pyridine complexes to study the interplay of stacking and hydrogen bonding. In particular, they showed that the H-bond capacity of pyridine is closely related to the electron-donating/withdrawing character of substituents on the benzene ring, while the stacking energy is less dependent on those properties.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The minimum Fukui function principle captures the irrelevance of the frontier orbitals but misses the fact that electrostatic interactions normally dominate hard-hard interactions. [67,68,72] In contrast to the well studied local softness, few studies of the local hardness are reported in the literature, mainly by our group using the local hardness as an indicator for charge concentration in studies on zeolite-catalyzed reactions, [73][74][75] noncovalent intermolecular interactions, [76][77][78][79][80] and local HSAB. [81] Then, one of the goals of this work is to see if the local hardness is able to locate the hardest reactive sites in a molecule.…”
Section: Introductionmentioning
confidence: 99%